Pengaruh Alumina Terhadap Membran Blend Kitosan-Polivinil Alkohol- LitiumSebagai Membran Elektrolit Baterai - Mesakh, Eka Putra; Napitupulu, Mery; Gonggo, Siang Tandi (Universitas Tadulako, 2017)
The research aim was to study the effect of adding % weight alumina on the conductivity of polymer electrolyte chitosan-PVA-lithium. The characterization of functional groups was determined using fourier transform infrared spectrometry (FTIR). The Ionic conductivity of polymer electrolyte chitosan-PVA-lithium-alumina was measured by using impedance spectroscopy. The measurement results show the polymer electrolyte with the addition of 5% alumina provides the highest ionic conductivity of 3.991 x 10-3S/cm. Battery characteristics of electrolyte polymer of chitosan-PVA-lithium with the addition of alumina have a voltage of 1.4 Volts compared to commercial batteries which have a voltage of 1.5 Volts. These results indicate that alumina can be used as a filler to increase the ionic conductivity.